Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1097/jsm.0000000000000722
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Multimodal Assessment of Concussion Recovery in Youth Athletes

Abstract: Objective: To evaluate recovery trajectories among youth athletes with a concussion and healthy controls across different domains using a quantitative and multifaceted protocol. Study Design: Prospective repeated measures. Participants: Youth athletes diagnosed with a concussion between the ages of 8 and 18 years were evaluated (1) within 10 days after injury, (2) approximately 3 weeks after injury, and (3) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Studies have been mixed in whether80 82 or not76 81 ERP latency was associated with SRC. Five studies indexed functional connectivity using various indices extracted from the proprietary brain network algorithm (BNA), all of which reported either significant SRC versus control group differences or different trajectories of BNA scores across groups 83–87…”
Section: Resultsmentioning
confidence: 99%
“…Studies have been mixed in whether80 82 or not76 81 ERP latency was associated with SRC. Five studies indexed functional connectivity using various indices extracted from the proprietary brain network algorithm (BNA), all of which reported either significant SRC versus control group differences or different trajectories of BNA scores across groups 83–87…”
Section: Resultsmentioning
confidence: 99%
“…The sample size calculation is based sample sizes from previous paper examining multimodal assessment, ~200 [ 18 , 35 ]. To determine the appropriate sample size (SS) for estimating the proportion of players we used the following formula ( Eq 1 ) as previously described.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, significant challenges remain in the monitoring and objective or personalised return to play (RTP) procedures. There is inconsistency in what tests are performed during participants RTP, varying widely from neurocognitive testing to visual assessment [ 17 , 18 ]. Our previous work outlines the deficiencies in current traditional assessment methods [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have found that concussion injuries have a negative impact on cognition, balance, and mobility, which recover at different rates post-concussion (6,7). Utilizing a functional performance test, as a part of a comprehensive examination of a concussion, may enable health clinicians to better determine the trajectory of recovery following a concussion (8)(9)(10)(11). A recent study suggested a new measure, the Gait Disorientation Test (GDT), which is the difference in the time needed to finish a 20-feet walking task between performing the task with eyes open and eyes closed (12).…”
Section: Introductionmentioning
confidence: 99%